Historical dictionary of the Indochina War (1945-1954) an international and interdisciplinary approach - Goscha, Christopher E. (Nordic Institute of Asian Studies reference library ;, 2015)
This first dictionary of the Indochina War to appear in English also adopts a path-breaking international and interdisciplinary approach to explore social, cultural and economic themes behind the conflict. In so doing, it demonstrates the remarkable international context of what once was regarded a simple Franco-Vietnamese war of decolonization.